2008
DOI: 10.1007/s10765-008-0422-0
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Melting Temperatures and Sources of Errors Using Two-Color Pyrometry During In-flight Measurements of Atmospheric Plasma-Sprayed Particles

Abstract: Growing demands on the quality of plasma-sprayed coatings require reliable methods to monitor and optimize the spraying processes. As the coating microstructures are dependent on the characteristics of the powder feedstock, particle in-flight diagnostics is of great importance. In particular, the melting status of the particles is critical in this regard. Thus, the accurate determination of the particle temperature is necessary. In-flight particle temperature measurements during atmospheric plasma spraying (AP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 27 publications
(32 reference statements)
2
9
1
2
Order By: Relevance
“…The other axis z is defined as the distance from the center of the plasma torch (the powder injection nozzle side is set to be negative) as shown in the schematic diagram the constant temperature of *2,780 K were also observed when R c and x varied. These results confirm the existence of a constant peak suggesting the emission of the latent heat previously reported by several authors when the input power, the plasma gas composition and flow rate were varied [16][17][18][19]. Note that the evolution of temperature distributions was not the same among R f , R c , and x.…”
Section: Effect Of Powder Feed Rate On Particle State Parameterssupporting
confidence: 89%
See 1 more Smart Citation
“…The other axis z is defined as the distance from the center of the plasma torch (the powder injection nozzle side is set to be negative) as shown in the schematic diagram the constant temperature of *2,780 K were also observed when R c and x varied. These results confirm the existence of a constant peak suggesting the emission of the latent heat previously reported by several authors when the input power, the plasma gas composition and flow rate were varied [16][17][18][19]. Note that the evolution of temperature distributions was not the same among R f , R c , and x.…”
Section: Effect Of Powder Feed Rate On Particle State Parameterssupporting
confidence: 89%
“…Thus, even two conditions with similar average in-flight particle temperatures can have significantly different distribution profiles in the particle temperatures involving multiple peaks reflecting the particle states. Although the relationship between the peaks and the particle states is not fully understood yet [16][17][18][19], these temperature distributions are important to tailor TBC microstructures. Thus, the loading effects need to be examined associated with the particle temperature distributions.…”
mentioning
confidence: 99%
“…Careful consideration of the particle temperature distributions has revealed their multi-modal nature ( Ref 11,12), which raises the fundamental question whether average (temperature) is sufficient to describe the distribution. Further analysis of the distribution by fitting for the underlying sub-distributions has shown the presence of one sub-distribution at the same temperature, which has been verified to be the melting point of the material ( Ref 11,13).…”
Section: Introductionmentioning
confidence: 86%
“…More information about DPV including equipment details, measurement principles, and error analysis can be found in references ( Ref 11,13,15) and in DPV equipment manual. Data were collected from large number of particles (~10,000) at the flow center (particle flux) of the spray stream at the spray distance of 130 mm and their distribution analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…This method assumes that the surface emissivity of the particles is independent of the wavelengths of measurement (Ref 29) (gray body assumption) which can cause distortions in the measurement. Previous study on statistical analysis of individual particle pyrometry has demonstrated that the melting temperature detected by the DPV-2000 sensor can differ up to 200°C from its real value ( Ref 30,31). In addition, the effect of possible plasma emissions scattering from the particle on the measured temperatures has been suggested by some authors ( Ref 32).…”
Section: Introductionmentioning
confidence: 96%